Unusual distal migrations of ventriculoperitoneal shunts: a six-patient pediatric case series with literature review - Gupta, Sunny; Sharma, Avinash; Sharma, Anand; Shukla, Avdhesh (International Journal of Research in Medical Sciences, 2025)
Distal migration of ventriculoperitoneal (VP) shunts to atypical sites is an uncommon but potentially serious complication. This retrospective case series presents six pediatric patients (aged 0-3 years) with unusual distal shunt migrations managed at a tertiary neurosurgical center between 2018 and 2025. Three infants exhibited scrotal migration through a patent processus vaginalis (PPV), two children presented with transanal extrusion following bowel perforation, and one infant had vaginal extrusion. Management included shunt revision with PPV ligation, shunt removal with antibiotic therapy, and definitive cerebrospinal fluid (CSF) diversion procedures, including endoscopic third ventriculostomy (ETV). All patients recovered without long-term morbidity. This study highlights the clinical importance of early recognition and prompt management of distal catheter migration, emphasizing preventive strategies, including optimizing catheter length and surgical correction of a PPV.